2014
DOI: 10.1007/s00401-014-1247-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutually exclusive mutations of KIT and RAS are associated with KIT mRNA expression and chromosomal instability in primary intracranial pure germinomas

Abstract: Intracranial germ cell tumors (iGCTs) are the second most common brain tumors among children under 15 in Japan. The pathogenesis of iGCTs is largely unexplored. Although a subset of iGCTs is known to have KIT mutation, its impact on the biology and patients' survival has not been established. In this study, we investigated genes involved in the KIT signaling pathway. 65 iGCTs (30 pure germinomas, 14 teratomas, 18 mixed GCTs, 2 yolk sac tumors, 1 choriocarcinoma) were screened for mutation of KIT, KRAS, NRAS, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 46 publications
3
85
2
Order By: Relevance
“…We have previously reported in our preliminary study that mutually exclusive mutations of KIT/RAS are found in 60 % of pure germinomas; they are, however, rare among NGGCTs, suggesting that there may be some genetic factors that determine the phenotypical diversity of GCTs [3]. A recent investigation using whole exome sequencing confirmed that mutations of KIT or RAS are the most frequent event in CNS GCTs, as well as identified several other genes including CBL, BCORL1 and MTOR as mutated in a subset of these tumors [24].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We have previously reported in our preliminary study that mutually exclusive mutations of KIT/RAS are found in 60 % of pure germinomas; they are, however, rare among NGGCTs, suggesting that there may be some genetic factors that determine the phenotypical diversity of GCTs [3]. A recent investigation using whole exome sequencing confirmed that mutations of KIT or RAS are the most frequent event in CNS GCTs, as well as identified several other genes including CBL, BCORL1 and MTOR as mutated in a subset of these tumors [24].…”
Section: Introductionmentioning
confidence: 80%
“…Design of the Ion AmpliSeq primers, Ion Torrent sequencing and the mutation call are described in the Supplementary Information. Selected mutations detected by either WES or Ion Torrent sequencing were confirmed by Sanger sequencing performed as previously described [3].…”
Section: Ion Torrent Sequencingmentioning
confidence: 99%
“…Such mutations are mutually exclusive and are positively correlated with KIT mRNA overexpression and chromosomal instability [28]. The importance of these findings is that molecular targeting agents, such as imatinib, which is an inhibitor of specific tyrosine kinases, including KIT, can be used in the management of GGCTs that harbor KIT mutations.…”
Section: Molecular Oncology Of Gctsmentioning
confidence: 99%
“…However, some suggest that patients with these mutations require long-term follow-up due to the risk of secondary GCTs [29]. Similar molecular and genetic findings have not been clearly uncovered in the pathogenesis of NGGCTs [28].…”
Section: Molecular Oncology Of Gctsmentioning
confidence: 99%
See 1 more Smart Citation